ISO certification and human resource management - Hassan, Arif (Indian Society for Labour Economics, 2009)
The paper empirically examines the employees’ perception of human resource HR) practices in ISO and non-ISO certified companies in Malaysia. A sample of 238 employees drawn from eight companies, four of them ISO-certified, responded to a questionnaire, which measured the adequacy of several HRM systems. The ISO-certified companies received higher endorsements on managing career systems, conducting contextual analysis for goal setting, and quality orientation. In the rest of the cases, the differences were not significant. The findings suggest that organisations need to go beyond quality assurance to organisation-wide quality management through improvement in HR systems and practices.